Math, asked by PranjalKumarDas, 1 year ago

Prove that
tanA/1-cotA + cotA/1-tanA = 1+secA cosecA

Answers

Answered by Anonymous
2
HEY DEAR ... ✌️

_______________________

_______________________


Here's , ur answer :-



Tan a/(1-cot a) +cot a/(1-tan a)


=(sin a/,cos a) /(1-cos a/sin a) + (cos a/sin a) /(1-sin a/cos a)


=sin ^2 a/cosa(sina - cosa) +cos^2 a/sina (cosa-sina)


=sin^2a/cosa(sina-cosa) - cos^2a/sina (sina-cosa)


=(sin^3a-cos^3a)/sina.cosa(sina-cosa)


=(sina-cosa)(sin^2a+cos^2a+sinacosa)/sina.cosa(sina-cosa)


=(1+sinacosa)/sina.cosa


=(1/sinacosa)+1


=1+seca.coseca


_______________________


HOPE , IT HELPS ... ✌️

PranjalKumarDas: can you please write it on a paper :)
Answered by Anonymous
10
thanks...........................
Attachments:

PranjalKumarDas: how did it became -ve
PranjalKumarDas: Thanks ;")
Anonymous: Nice answer Riya . But anyways ... my solution was also same . LoL
PranjalKumarDas: But I refer Riya's Ans for beginers like me LOL
Anonymous: okk ... No problem . ✌️
Similar questions